2013
DOI: 10.1007/s00401-013-1209-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1 overexpression and Trp53 haploinsufficiency cooperatively promote de novo malignant peripheral nerve sheath tumor pathogenesis

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are Schwann cell-derived malignancies that arise from plexiform neurofibromas in patients with mutation of the neurofibromin 1 (NF1) gene. We have shown that the growth factor neuregulin-1 (NRG1) also contributes to human neurofibroma and MPNST pathogenesis and that outbred C57BL/6J x SJL/J transgenic mice overexpressing NRG1 in Schwann cells (P0-GGFβ3 mice) recapitulate the process of neurofibroma-MPNST progression. However, it is unclear whether NRG1 acts pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…On average, there were 67 mutations per tumor categorized as variants in: 1) genes associated with MPNST; 2) genes previously reported to be mutated in other cancers; or 3) mutations for which the clinical significance is currently unknown (Table ). Mutations were identified in 4 genes previously implicated in MPNST pathogenesis in both human studies and genetically engineered mouse models ( NF1, TP53, EGFR , and PDGFR‐α [ PDGFRA ]) . Variants also were identified in other genes potentially involved in MPNST pathogenesis ( GNAQ, SLCO1B1, LAMA2, SLC34A2, PTCH1, RB1, KDR, CYP2A6, MYC, FLT4 , and PSMD2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…On average, there were 67 mutations per tumor categorized as variants in: 1) genes associated with MPNST; 2) genes previously reported to be mutated in other cancers; or 3) mutations for which the clinical significance is currently unknown (Table ). Mutations were identified in 4 genes previously implicated in MPNST pathogenesis in both human studies and genetically engineered mouse models ( NF1, TP53, EGFR , and PDGFR‐α [ PDGFRA ]) . Variants also were identified in other genes potentially involved in MPNST pathogenesis ( GNAQ, SLCO1B1, LAMA2, SLC34A2, PTCH1, RB1, KDR, CYP2A6, MYC, FLT4 , and PSMD2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified gene expression changes in MPNST’s with loss of PRC2 function (Lee et al 2014), and we found some of the same changes in our Eed cKO mice. More specifically, Eed cKO led to an upregulation of Nrg1 , which is also observed in neoplastic Schwann cells within human neurofibromas and MPNST’s (Stonecypher et al 2005), and aberrant NRG1 signaling contributes to the pathogenesis of neurofibromas and MPNST’s in mouse models (Brosius et al 2014; Gomez-Sanchez et al 2013; Huijbregts et al 2003; Kazmi et al 2013). In addition, SEMA4F-deficiency was also identified in models of Neurofibromatosis type 1 and human neurofibromas, and appears to be a mechanism of loss of Schwann cell-axonal interaction, which contributes to tumorigenesis (Parrinello et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…To determine whether NRG1 interacts with Nf1 or Trp53 loss, cohorts of inbred P 0 -GGFb3;Nf1 þ/À and P 0 -GGFb3;Trp53 þ/À mice were established and examined for evidence of tumor formation. 97 Although no tumors were seen in P 0 -GGFb3;Nf1 þ/À mice, virtually all of the P 0 -GGFb3;Trp53 þ/À mice developed MPNSTs. The MPNSTs in P 0 -GGFb3;Trp53 þ/À mice, like those in cis-linked Nf1 þ/À ; Trp53 þ/À mice, arose de novo, demonstrating that NRG1 overexpression could substitute for Nf1 loss and thus must promote tumorigenesis through the same signaling cascade affected by Nf1 loss.…”
Section: Currently Available Mouse Models Of Neurofibroma and Mpnst Pmentioning
confidence: 96%
“…transcriptome sequencing experiments have recently been presented at national meetings, only aCGH results are published, 96,97,100 and so I focus on those experiments here.…”
Section: Currently Available Mouse Models Of Neurofibroma and Mpnst Pmentioning
confidence: 99%
See 1 more Smart Citation